MANAJEMEN LABA PADA PERUSAHAAN BASIC MATERIAL - Faisal, Yusuf; Oktaviani, Resty Fuji; Sari, Egi Gumala (Worksheet : Jurnal Akuntansi, 2024)
This research was conducted ti observing 98 basic material listed on the Indonesia Stock Exchange. The data source used is the company’s annual report from 2012-2022. This study aims to obtain empirical evidence on the influence of intellectual capital , tax planning , and leverage   with institutional ownership as a moderating variable. The result of this study found that intellectual capital  has a positive and statistically effect on earnings management, while tax planning  has a positive and statistically insignificant effect on earnings management, leverage   has a positive and statically insignificant effect on eanings management. Furthermore, institutional ownership strengthens the influence of intellectual capital  on earnings management. Institutional ownership weakens the influence of tax planning  on earnings management. Institutional ownership also reinforces the effect of leverage   on earnings management.